(untitled) (Bangladesh Rice Journal, 2025)
A field experiment was carried out with six genotypes of Boro season rice at Sadar Upazila of Khagrachhari district, Bangladesh. The study evaluated the genetic variability, heritability, correlations among the studied traits, and their direct effect on yield. The research result revealed that the phenotypic variance was higher than the genotypic variance for all the measured traits. High phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) values were observed for grain yield (GY), thousand-grain weight (TGW), days to flowering (DTF), days to maturity (DTM), plant height (PH), panicle length (PL), number of filled grains per plant (FG), and number of unfilled grains per plant (UFG), indicating a very high heritability estimate. The calculated genetic advance as a percent of the mean for all traits was also very high. The GY was positively correlated with PH, DTM, and the number of total tillers per hill (NTH), PL, FG, UFG, and TGW; and negatively correlated with DTF and the number of non-effective tillers per hill (NETH). Principal component analysis revealed that PC1 exhibited the highest standard deviation (267.95) and proportion of variance (88%), with subsequent principal components showing gradual reduction. However, in terms of cumulative proportion, the contributions of the principal components were similar, except for PC1. Path analysis revealed that DTM, number of effective tillers per hill (ETH), PL, FG, UFG, and TGW directly affect GY. FG (0.526), PL (0.394), UFG (0.205), and ETH (0.192) showed a highly significant positive correlation contributed to the GY in path analysis; indicating that selecting these traits might be effective in improving grain yield in the future breeding programs. Bangladesh Rice J. 27(2): 51-65, 2023